Effect of land set up systems on soil losses - Napoli, Marco; Altobelli, Filiberto; Orlandini, Simone (Italian Journal of Agronomy, 2020)
Agricultural land set up systems comprise those agronomic structures able to preserve the soil fertility from water erosion, such as: ditching, contouring, earth-riser and stonewall terracing, draining, and channelization, etc.. However, in the past 60 years, agricultural mechanization has led to an expansion of the field size and reduction in land set up system intensity to make machine operation more feasible and cheaper. As a consequence, these transformations have made sloping fields less resilient to the storms and accelerated the soil erosion processes. Based on an 8- year field study in ‘Chianti Classico’ area (Tuscany, Central Italy), this research aimed to evaluate the effectiveness of the land set up systems such as diversion ditch, earth-riser and stonewall terracing on reducing water erosion from field crops, olive orchards, and vineyards. The results showed that diversion ditches were effective on herbaceous crop fields with slope steepness lower than 9%. While, for higher slopes, diversion ditches were not sufficient to contain the soil loss within OECD 2008 tolerable limits in none of the considered land uses. On the opposite, in steep slopes, earth-riser terraces and stonewall terraces have shown their value as land set up system capable of reducing the erosive process. Their greatest drawback is the reduction of the cultivable surface deriving from the presence of the riser and the walls. However, their added value as a precious element characterizing the local landscape was of considerable importance for the local economy linked to tourism. Highlights - Diversion ditches reduce soil erosion on herbaceous crop fields with slope lower than 9%. - Diversion ditches did not contain the soil loss within acceptable limits on steep slopes. - Earth-riser terraces and stonewall terraces reduced soil losses within acceptable limits. - Terraces reduced soil loss by 4.7-12.3 times with respect to diversion ditches. - The analysis was performed on measured average annual soil loss data from 695 fields.